The Lecturer’s Attitude in Written Feedback Towards Students’ Teaching Performance on Microteaching Course: An Appraisal Analysis - Lesmana, Alya Zilva Putri; Hartati , Elysa (Edu-Ling: Journal of English Education and Linguistics, 2023)
This study examines how a lecturer at a university in Yogyakarta provides written feedback to student teachers in microteaching courses and the underlying ideology behind it. The language used by the lecturer is analyzed using appraisal theory to understand their views on the course and the student teachers. Descriptive qualitative research methodology is used in this study and data was obtained from a lecturer who taught microteaching courses. The data consists of feedback provided to 16 students, revealing 196 attitudes in the written feedback. The dominant attitudes are positive judgment, followed by negative judgment, positive appreciation, negative affect, negative appreciation, and positive affect. The study finds that the lecturer's ideology aligns with a pedagogical perspective emphasizing positive character traits and the reinforcement of these traits in teaching and learning. The lecturer's approach prioritizes positive reinforcement, constructive guidance, and recognition of achievements. The study provides insights into the lecturer's attitudes in giving written feedback, offers guidance for teachers in providing proper feedback to students, and gives an innovation regarding exploring the data used for learning an appraisal theory for future research.